Modelagem da rugosidade de insertos de metal duro com base na topografia do rebolo - Costa, Hugo Emanoel de Andrade (Universidade Federal de São Carlos, 2023)
After sintering, cemented tungsten carbide cutting inserts are ground so that the final dimensions can be obtained and surface defects can be reduced. To quantify the insert surface quality after the finishing process, different roughness parameters are measured, which depend on the process conditions and, mainly, on the grinding wheel topography. In order to reduce carrying out experiments to determine the conditions that lead to optimal roughness values, which involves consumption of time and resources, several analytical and numerical models have been applied. In this research, however, it is proposed the use of a graphic model, elaborated through CAD software, based not only on the kinematics of the process, but also on the characteristics of the grinding wheel topography and of the workpiece, such as geometry and spatial distribution of the abrasive grits. As obtained through the graphic models, the Rayleigh distribution used to position the grit about to its protrusion, grinding wheels with smaller grain protrusion and inserts with lower initial roughness led to lower values of final roughness. For the surfaces simulated with the real grinding wheel topography, in general, it was observed that higher grain protrusion or number of active cutting edges caused an increase in roughness, as the surface was significantly modified.
Modeling of the roughness of carbide inserts based on the topography of the grinding wheel
Keywords: Usinagem; Integridade superficial; Grãos abrasivos; Processo de retificação; Modelo gráfico; Machining; Surface integrity; Abrasive grits; Grinding process; Graphic model; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO